Gross Motoric Before and After Given the Stimulation of Games in Kindergarten As Syariah Jember - Happy Anggi D; Jamhariyah; Susilawati (Health and Technology Journal (HTechJ), 2023)
This study employed a pre-experimental research design with a population of 29 respondents. A sample of 27 respondents was selected using simple random sampling. Data collection was conducted using observation sheets, and data analysis was performed using the Paired Sample t test test. The study revealed that prior to engaging in the traditional game of snakes and ladders, all respondents were categorized as having underdeveloped gross motor skills (BB) (100%). However, after playing the traditional game of snakes and ladders, most respondents were classified as having significantly improved gross motor skills (BSB) (93%). The analysis indicated a significant influence of the traditional game of snakes and ladders on gross motor skills in children, with a significant result (2-tailed 0.000 ≤ 0.05). The difference in gross motor skills in kindergarten children before and after being given stimulation through the Snakes and Ladders Game has a positive effect on children's gross motor skills. Playing snakes and ladders provides stimulation that can enhance the gross motor skills of children aged 4-5 years. Therefore, the traditional game of snakes and ladders can be used as a stimulation tool to optimize the development of underdeveloped gross motor skills.